2015
DOI: 10.1016/j.celrep.2015.06.019
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Machinery of Neurodegeneration in In Vitro Models of Amyotrophic Lateral Sclerosis

Abstract: Summary Neurodegenerative phenotypes reflect complex, time-dependent molecular processes, whose elucidation may reveal neuronal class-specific therapeutic targets. The current focus in neurodegeneration has been on individual genes and pathways. In contrast, we assembled a genome-wide regulatory model (henceforth, interactome), whose unbiased interrogation revealed 23 candidate causal master regulators of neurodegeneration in an in vitro model of amyotrophic lateral sclerosis (ALS), characterized by a loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 40 publications
8
51
0
Order By: Relevance
“…In addition, their use in non-cancer phenotypes has helped to elucidate an equivalent disease checkpoint architecture in neurological phenotypes — including amyotrophic lateral sclerosis (ALS) 53 , Alzheimer disease 7,54 , Parkinson disease 55 and alcohol addiction 56 — and in developmental phenotypes, from regulation of germinal centre formation 39 to stem cell pluripotency 57 . As briefly summarized below, these examples further outline the role of tumour checkpoint MRs in regulating disease dystasis and their unique nature compared with their physiological counterpart involved in homeostatic control.…”
Section: Mr and Tumour Checkpoint Elucidationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, their use in non-cancer phenotypes has helped to elucidate an equivalent disease checkpoint architecture in neurological phenotypes — including amyotrophic lateral sclerosis (ALS) 53 , Alzheimer disease 7,54 , Parkinson disease 55 and alcohol addiction 56 — and in developmental phenotypes, from regulation of germinal centre formation 39 to stem cell pluripotency 57 . As briefly summarized below, these examples further outline the role of tumour checkpoint MRs in regulating disease dystasis and their unique nature compared with their physiological counterpart involved in homeostatic control.…”
Section: Mr and Tumour Checkpoint Elucidationmentioning
confidence: 99%
“…Postgenomic research has seen intense interest in the systematic dissection of the transcriptional and signalling logic of cancer cells (henceforth termed regulatory logic) 48,53,5557 , including its transcriptional 5860 , post-transcriptional 6163 and post-translational 6468 layers. These methods were first developed and validated in bacteria 69 and yeast 70,71 and then extended to mammalian cells 21,59 , thus complementing pre-existing literature-curated models 72 and large-scale experimental assays 73 .…”
Section: Mr and Tumour Checkpoint Elucidationmentioning
confidence: 99%
“…Indeed, virtually none of the regulators that were experimentally validated were significantly differentially expressed at the RNA level and yet they were confirmed as individual or synergistic phenotypic drivers following identification by regulatory network analysis, thus elucidating novel mechanisms of disease initiation/ progression [4,12,13,[41][42][43][44][45][46], chemosensitivity [15,28], and normal physiologic regulation [14]. Lately, we have successfully extended these methodologies to the study of neurological, neurodevelopmental, and stem cell phenotypes [35,42,47], and, more recently, to neurodegenerative phenotypes, resulting in a series of manuscripts, currently in review, where we report on the elucidation and experimental validation of novel genes mediating neurotoxicity in ALS [48], as well as biomarkers of AD progression [9].…”
Section: Creating the Assembly Manual Of The Alzheimer's Cellmentioning
confidence: 99%
“…Moreover, CD2 is not expressed in neural cells 21 , which were the target cells to purify. Importantly, cells expressing CD2 have not showed any detectable phenotypes when compared to parental lines 22 . Under the conditions established in this study, motoneurons were functionally mature after only 4 days of culture, as indicated by robust firing of APs (Figure 2C).…”
Section: Discussionmentioning
confidence: 98%